Electronic tax filing adoption and its impact on tax employees performance in Jordan: a proposed framework - Alibraheem, Mohammad Haider; Abdul Jabbar, Hijattulah (International Digital Organization for Scientific Information (IDOSI), 2016)
Technology adoption does not only influence end-user, it also improves employee performance as well. Task-Technology-Fit Theory highlights the link between technology adoption and employee performance, however studies are rare in the context of taxation. This paper discusses whether electronic tax filing (ETF) adoption improves the employee performance in the Jordanian Tax Offices. By utilizing the unified theory of acceptance and use of technology (UTAUT), the paper proposes a framework on the antecedents of electronic tax filing and its impacts on employee performance of the Jordanian Tax Offices. The proposed framework could give significant practical insight and implication to tax authorities worldwide that implement ETF, especially the Jordanian Tax Office.